Dry arthroscopic 4-corner arthrodesis and other refinements to stay within a tourniquet time - Ruas, Jaime S.; del Pinal, Francisco; Mazarrasa, Raquel (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
4-corner arthrodesis is a widely implanted procedure to treat degenerated joints in the wrist such as SLAC and SNAC stage II and III. Arthroscopy in combination with headless cannulated screws, permits reproducing the same intervention with the advantages of a minimally invasive surgery. This technique has already been published in the past supported by the early experience in this new exciting field. The purpose of this paper is to present new technical refinements collected over the years in order to speed up the surgery while obtaining optimum results. In this paper we also present extreme scenarios solved by combining the scope with cannulated screws.
Keywords: Dry arthroscopy; 4-Corner arthrodesis; partial wrist arthrodesis; total wrist arthrodesis